Magnetic Properties of Igneous Rocks from Banyuwangi, East Java And Their Reliability for Paleomagnetic Study - La Ode Ngkoimani; Satria Bijaksana; Mahrizal Mahrizal; Chalid Idham Abdullah; The Houw Liong (Indonesian Journal of Physics, 2005)
We have measured 78 oriented specimens taken form two igneous intrusions in Gunung Nangkajajar at the eastern tip of Java near the town of Banyuwangi for rock magnetic and paleomagnetic investigations. The two intrusions are then referred to as ANBW and DINJ respectively. Upon magnetic measurements, ANBW specimens are found to be magnetically stronger than their DINJ counterparts are. Nevertheless, the specimens in the two sites are suitable for paleomagnetic study as they are magnetically quite isotropic with percent anisotropy well below 10% and magnetic remanence that are stable and consistent upon demagnetization. The consistency of remanence is indicated by the low value of limit or size of cone of confidence, simply referred to as α95 and by the high value of precision parameter k. The results show that paleolatitude of these intrusions was about thirty degree South (30° S), which is far south than their present position. The actual motion of these sites is still being investigated, as no absolute age is known for them. Nevertheless, these paleomagnetic finding is very important as no paleomagnetic data ever existed for the eastern tip of Java.